2012
DOI: 10.1254/jphs.12085fp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TAK-480, a Novel Tachykinin NK2^|^ndash;Receptor Antagonist, on Visceral Hypersensitivity in Rabbits and Ricinoleic Acid^|^ndash;Induced Defecation in Guinea Pigs

Abstract: Abstract. TAK-480, 4-(difluoromethoxy)-N-((1R,2S)-2-(((3aR,4R,9bR)-4-(methoxymethyl)-2, 3,3a,4,5,9b-hexahydro-1H-pyrrolo[3,2-c]quinolin-1-yl)carbonyl)cyclohexyl)benzamide, is a novel tachykinin NK 2 -receptor antagonist. In this study, we investigated its antagonistic activity and efficacy in animal models of visceral hypersensitivity and stimulated bowel function which have been implicated to underlie the symptoms in irritable bowel syndrome (IBS). TAK-480 showed potent binding affinity for human NK 2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Tachykinin NK-2 receptor is a major factor in tachykinin-induced smooth muscle contraction in human colon smooth muscle in vitro; the response consists of an excitatory component via direct action on the smooth muscle and an inhibitory component, possibly via nitrergic neurons (31). In a rabbit model of intracolonic zymosan-induced visceral hypersensitivity, the tachykinin NK-2 receptor antagonist, TAK-480, markedly inhibited the visceromotor response to colorectal distension (32), suggesting a reduction in visceral sensitivity.…”
Section: New Classes Of Drugsmentioning
confidence: 99%
“…Tachykinin NK-2 receptor is a major factor in tachykinin-induced smooth muscle contraction in human colon smooth muscle in vitro; the response consists of an excitatory component via direct action on the smooth muscle and an inhibitory component, possibly via nitrergic neurons (31). In a rabbit model of intracolonic zymosan-induced visceral hypersensitivity, the tachykinin NK-2 receptor antagonist, TAK-480, markedly inhibited the visceromotor response to colorectal distension (32), suggesting a reduction in visceral sensitivity.…”
Section: New Classes Of Drugsmentioning
confidence: 99%
“…Among the three tachykinin receptor subtypes, NK2 receptors have an important role in regulating human colonic motility. Numerous pharmacological studies using human colonic smooth muscle strips have revealed that the contractile effects of endogenous tachykinins are mediated by NK2 receptors (Croci et al, 1998;Cao et al, 2000;Liu et al, 2002;Liu et al, 2009;Nakamura et al, 2011;Tanaka et al, 2012). This is in line with the high mRNA expression levels of the TACR2 gene (encoding NK2 receptors) in human colonic smooth muscle (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 62%
“…Mustard oil, given orally, induces elongation of the transit time in the upper GI (esophagus) and a decreased transit time in the lower GI part (colon) (271). Ricinoleic acid-induced defecation in the guinea pig is suppressed by a specific tachykinin receptor NK2 antagonist (272).…”
Section: Non-rodent Modelsmentioning
confidence: 99%
“…In rabbits, intracolonic infusion of Zymosan leads to colonic hypersensitivity (272) which is reduced by a tachykinin NK2 receptor antagonist.…”
Section: Non-rodent Modelsmentioning
confidence: 99%